A comparative study between glulam and concrete columns in view of design, economy and environment. (June 2022) - Hassan, Osama A.B.; A.A., Nour Emad; Abdulahad, Gabriel
Abstract: In this paper, it is attempted to study possible sustainability solutions for building structures. In this context, comparisons are made between two load-bearing columns with different building materials – glued laminated timber and concrete – with regard to structural design, economic consequences and the emission of greenhouse gases. In terms of structural design, the results show that with small axial forces, glulam columns will result in smaller cross-sectional areas compared to concrete columns. However, at larger axial forces, concrete columns will result in smaller cross-sectional areas than glulam columns. An increased column length also means larger dimensions for glulam columns, but this does not always apply to concrete columns. With respect to environmental impact, it is shown that using glulam columns is the more environmentally friendly option. From an economic point of view, the cost estimates for glulam and concrete columns may vary depending on the country and the abundance of the construction material. In Sweden, a forest-rich country, it is shown that the costs for both column types are quite similar considering small axial loads. At higher axial loading, concrete is generally the cheaper alternative.